COMPARATIVE ANALYSIS OF ALUMINUM AND STEEL MECHANICAL PROPERTIES - R.A Abdul Kadir; S. Abdullah; A.A Mohd Yusuf; K. Md Isa; A.W. Mohd Arhafudin (Marine Frontier, 2023)
This research compares and evaluatesthe mechanical properties of steel and aluminum for lightweight usage in industrial appliances and aircraft parts. Physical and mechanical characteristics, which establish a material’s characteristics in terms of strength, hardness, ductility, stiffness, and microstructure analysis, describe its mechanical properties. Producing lightweight industrial appliances and high-performance aviation components is hampered by researchers’ and manufacturers’ incapacity to choose the appropriate materials. This study aims to compare and evaluate the mechanical properties of aluminum and steel while considering theoretical analysis. According to the experimental findings, steel fractures more quickly during the tensile test because it has a higher tensile strength than aluminum. Steel had a tensile strength of 60.495 MPa while aluminum had a tensile strength of 33.609 MPa. The data points at 8.73E+00 and 4.59E+02 on the graph illustrating the relationship between load and displacement for aluminum demonstrate that the curve initially had a broad linear association before fracturing. As soon as the aluminum cracked, the load decreased. Comparably, the steel load-displacement graph displayed a generally linear connection up until a substantial rise in load, after which there was a displacement and another drop till the point of fracture (7.97E+00, 8.02E+02). The study’s findings emphasize how crucial it is to take into account the unique mechanical characteristics of various materials when creating lightweight components. Researchers and manufacturers can improve the performance and efficiency of industrial appliances and aviation parts by making well-informed decisions based on their understanding of these qualities. Because steel fractures more easily during tensile testing, it might not be the best material for these kinds of applications. Aluminum, on the other hand, has a lower tensile strength but a higher ductility.